Ternary Metal Phosphide with Triple-Layered Structure as a Low-Cost and Efficient Electrocatalyst for Bifunctional Water Splitting - Yu, Jing; Li, Qianqian; Li, Yuan; Xu, Cheng-Yan; Zhen, Liang; Dravid, Vinayak P.; Wu, Jinsong (Advanced functional materials, 2016)
Development of low‐cost, high‐performance, and bifunctional electrocatalysts for water splitting is essential for renewable and clean energy technologies. Although binary phosphides are inexpensive, their performance is not as good as noble metals. Adding a third metal element to binary phosphides (Ni‐P, Co‐P) provides the opportunity to tune their crystalline and electronic structures and thus their electrocatalytic properties. Here, ternary phosphide (NiCoP) films with different nickel to cobalt ratios via an electrodeposition technique are synthesized. The films have a triple‐layered and hierarchical morphology, consisting of nanosheets in the bottom layer, ≈90–120 nm nanospheres in the middle layer, and larger spherical particles on the top layer. The ternary phosphides exhibit versatile activities that are strongly dependent on the Ni/Co ratios and Ni0.51Co0.49P film is found to have the best electrocatalytic activities for both hydrogen evolution reactions and oxygen evolution reactions. The high performance of the ternary phosphide film is attributed to enhanced electric conductivity so that reaction kinetics is accelerated, enlarged surface area due to the hierarchical and three‐layered morphology, and increased local electric dipole so that the energy barrier for the water splitting reaction is lowered. Bimetallic phosphide (Ni0.51Co0.49P) films with a triple‐layered and hierarchical morphology with superior performance toward overall water splitting are successfully synthesized. The phosphides present versatile activities that are strongly dependent on the Ni/Co ratios. The improvement in performance is mainly ascribed to the alloying effect between Ni and Co atoms.